Analisis Buku Fun Learning Jago Bahasa Arab Basic 1 (Tinjauan Kelayakan Isi, Penyajian, Bahasa dan Kegrafikan) - Rianda Ayu Ritnaning Tias; Sihono (Mahira: Journal of Arabic Studies & Teaching, 2024)
The selection and use of appropriate textbooks is very important in supporting the effectiveness of learning, especially at the primary education level. The number of textbooks on the market with various qualities requires an objective evaluation of the feasibility of textbooks. This study aims to analyze the feasibility of the Fun Learning Jago Arabic Basic 1 book based on four aspects of assessment from BSNP, namely content, presentation, language, and graphics. This research uses a qualitative approach of library research with data collection through document analysis and semi-structured interviews with the author of the book. The results showed that the book obtained an average score of 3.41 (good) for content eligibility, 3.22 (good) for presentation, 3.41 (good) for language, and 3.76 (excellent) for graphics. The book excels in visual design, integration of audio-visual media, and presentation of contextualized and fun material for children. However, shortcomings were found in grammatical accuracy, presentation structure, and completeness of supporting elements such as SK-KD and glossary. In conclusion, this book is feasible to be used as Arabic teaching materials in elementary schools with a note of improvement on several aspects to increase learning effectiveness.